Quantification of biofilms in multi-spectral digital volumes from confocal laser-scanning microscopes - Rodenacker, Karsten (Image analysis and stereology, 2000)
Populations of bacteria in sludge flocs and biofilm marked by fluorescence marked with fluorescent probes are digitised with a confocal laser scanning microscope. These data are used to analyse the microbial community structure, to obtain information on the localisation of specific bacterial groups and to examine gene expression. This information is urgently required for an in-depthunderstanding of the function and, more generally, the microbial ecology of biofilms. Methods derived from quantitative image analysis are applied to digitised data from confocal laser scanning microscopes to obtain quantitative descriptions of volumetric, topological (and topographical) properties of different compartments of the components under research. In addition to free-moving flocs, also biofilms attached to a substratum in an experimental environment are analysed. Growth form as well as interaction of components are quantitatively described. Classical measurements of volume and intensity (shape, distribution) and distance dependent interaction measurements using methods from mathematical morphology are performed. Mainly image (volume) processing methods are outlined. Segmented volumes are globallyand individually (in terms of 3D-connected components) measured and used for distance mapping transform as well as for estimation of geodesic distances from the substrate. All transformations are applied on the 3D data set. Resulting distance distributions are quantified and related to information on the identity and activity of the probe-identitied bacteria.
Keywords: bakterije; In situ hybridization, fluorescence; Microscopy, confocal; genetika; Image processing, computer-assisted; rast; Bacteria; biofilm; Genetics; mikroskopija; analiza slik; Growth and development; Biofilms; matematična morfologija; fluorescenca; Sewage; Microscopy, electron; laserski skener